Global agricultural intensification during climate change: a role for genomics. Issue 4 (11th September 2015) - Abberton, Michael; Batley, Jacqueline; Bentley, Alison; Bryant, John; Cai, Hongwei; Cockram, James; Costa de Oliveira, Antonio; Cseke, Leland J.; Dempewolf, Hannes; De Pace, Ciro; Edwards, David; Gepts, Paul; et al.
Summary: Agriculture is now facing the 'perfect storm' of climate change, increasing costs of fertilizer and rising food demands from a larger and wealthier human population. These factors point to a global food deficit unless the efficiency and resilience of crop production is increased. The intensification of agriculture has focused on improving production under optimized conditions, with significant agronomic inputs. Furthermore, the intensive cultivation of a limited number of crops has drastically narrowed the number of plant species humans rely on. A new agricultural paradigm is required, reducing dependence on high inputs and increasing crop diversity, yield stability and environmental resilience. Genomics offers unprecedented opportunities to increase crop yield, quality and stability of production through advanced breeding strategies, enhancing the resilience of major crops to climate variability, and increasing the productivity and range of minor crops to diversify the food supply. Here we review the state of the art of genomic‐assisted breeding for the most important staples that feed the world, and how to use and adapt such genomic tools to accelerate development of both major and minor crops with desired traits that enhance adaptation to, or mitigate the effects of climate change.